ROLE OF FIRST-TRIMESTER ULTRASOUND (UP TO 12 WEEKS) IN EARLY PREGNANCY CARE: A RETROSPECTIVE OBSERVATIONAL STUDY - MUNAGALA SAHITHI; GAUTAM MUTHU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: To evaluate the diagnostic and descriptive role of first-trimester ultrasound (FTU) in early pregnancy at a tertiary healthcare center. Methods: A retrospective observational study was conducted in which 120 pregnant women who underwent FTU (≤12 weeks gestation) between March 2024 and February 2025. Archived imaging and hospital records were reviewed to analyze obstetric and ultrasound data. Outcomes assessed included gestational age confirmation, detection of fetal cardiac activity, yolk sac evaluation, and diagnosis of early pregnancy complications. Statistical analysis was performed using the Statistical Package for the Social Sciences v23.0. Results: Of the 120 cases, 77.5% were viable singleton intrauterine pregnancies. Multifetal gestation was identified in 5.8% with chorionicity assessment possible in all twin pregnancies. Ectopic pregnancies and anembryonic gestations were each diagnosed in 5% of cases. Embryonic cardiac activity was present in 83.3% and yolk sac abnormalities were noted in 11.6%. The nuchal translucency was measured in 16.6% of cases (Mean NT 1.34±0.29 mm). Additional findings included subchorionic hematomas (3.3%) and adnexal masses (4.2%). Crown-rump length-based gestational dating closely agreed with last menstrual period-based estimates. Conclusion: FTU plays an important role in early pregnancy care by ensuring early diagnosis of both normal as well as abnormal pregnancies. It improves obstetric decision-making through accurate dating, identification of viability, and early detection of complications.